2011
DOI: 10.13057/biodiv/d120401
|View full text |Cite
|
Sign up to set email alerts
|

Leaf endophytic fungi of chili (Capsicum annuum) and their role in the protection against Aphis gossypii (Homoptera: Aphididae)

Abstract: Hernawati H, Wiyono S, Santoso S (2011) Leaf endophytic fungi of chili (Capsicum annuum) and their role in the protection againstAphis gossypii (Homoptera: Aphididae). . The objectives of the research were to study the diversity of leaf endophytic fungi of chili, and investigate its potency in protecting host plants against Aphis gossypii Glov. Endophytic fungi were isolated from chili leaves with two categories: aphid infested plants and aphid-free plants, collected from farmer's field in Bogor, West Java. Ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 29 publications
0
11
0
2
Order By: Relevance
“…Studies conducted by Paul et al [37] reveal an assorted diversity of endophytic microorganisms in chili pepper, including some entomopathogens as Paecilomyces, Cordyceps, Cladosporium, and Penicillium; however, the authors do not report the natural presence of B. bassiana. Recent studies on chili and sweet pepper demonstrated the endophytic colonization of B. bassiana, and these are some examples of the limited numbers of reports about the colonization on this species [38,39].…”
Section: Endophytic Colonization Of Beauveria Bassiana Strainsmentioning
confidence: 99%
“…Studies conducted by Paul et al [37] reveal an assorted diversity of endophytic microorganisms in chili pepper, including some entomopathogens as Paecilomyces, Cordyceps, Cladosporium, and Penicillium; however, the authors do not report the natural presence of B. bassiana. Recent studies on chili and sweet pepper demonstrated the endophytic colonization of B. bassiana, and these are some examples of the limited numbers of reports about the colonization on this species [38,39].…”
Section: Endophytic Colonization Of Beauveria Bassiana Strainsmentioning
confidence: 99%
“…Hal tersebut disebabkan karena morfologi koloni cendawan endofit dapat berubahubah, sebagian cendawan endofit tumbuh sangat lambat dan sering kali tidak terjadi sporulasi (Hyde dan Soytong 2008). Tiga dari 5 isolat cendawan endofit yang diperoleh Hernawati et al (2011) dapat diidentifikasi berdasarkan pada morfologi koloni dan spora yang terbentuk, sedangkan 2 isolat lainnya merupakan hifa steril sehingga identitasnya hanya dapat diketahui melalui teknik PCR yang dilanjutkan dengan perunutan DNA.…”
Section: Pembahasanunclassified
“…At the end of their experiments, 26-60% of the Trichoderma-treated plants were free of symptoms, while in the control only 0-10% stayed healthy. In yet another study, the presence of endophytic fungi has been shown to inhibit the growth, virility, and reproduction of the aphid Aphis gossypii [17]. Some fungal strains even seem appropriate for biological protection, as demonstrated by Martinuz et al, who induced systemic resistance to Aphis gossypii using Fusarium oxysporum Fo162 and Rhizobium etli G12 strains [18].…”
Section: Introductionmentioning
confidence: 96%